The Personal Foundations of Political Tolerance towards Immigrants. - Freitag, Markus; Rapp, Carolin (Journal of Ethnic & Migration Studies, 2015)
In this paper, we expand previous research on the psychological foundations of attitudes towards immigrants by evaluating the role of the Big Five personality traits with regard to the formation of political tolerance. Following the literature, we elaborate tolerance as a sequential concept of rejection and acceptance to uncover differentiating effects of personality on both immigrant-specific prejudices as well as on the assignment of the right to vote as a pivotal political privilege to this group. Using a representative sample of the Swiss population, with its distinctive history related to the immigration issue, our two-step Heckman selection models reveal that extroverts and people who score low in agreeableness exhibit negative attitudes towards immigrants. At the same time, only openness to experience is significantly connected to the likeliness of granting immigrants the right to vote.